High fidelity walkthroughs in archaeology sites - Santos, Luís Paulo (2005)
Comunicação apresentada no 6th International Symposium on Virtual Reality, Archaeology and Cultural Heritage (VAST 2005), Pisa, Italy, 8-11 Novembro 2005.